Population-based Prostate Cancer Screening in Kazakhstan - Yevgeniy ISHKININ; Alma ZHYLKAIDAROVA; Nurzhan NURGALIYEV; Elmira AUYEZOVA; Ainash OSHIBAYEVA; Nadezhda GORBUNOVA (Tehran University of Medical Sciences, 2017)
Background: Issues of mass screening for prostate cancer rather controversial since 2013 in 11 regions of Kazakhstan introduced a population-based screening for prostate cancer, so we need to evaluate its results. Methods: In different regions of Kazakhstan during 2013-2015, a total of 321548 prostate-specific antigens (PSA) were determined in men aged 50-66 yr, under the Prostate Health Index (PHI) and transrectal ultrasonography (TRUS) guided prostate biopsy with histological examination. Results: PSA level up to 4 ng/ml in 310870 (96.7%) men, PSA level between 4 and 10 ng/ml in 8 624 (2.7%) men, PSA level above 10 ng/ml in 2054 (0.6%) men. PHI was identified in 5716 (1.8%) men, of which 2867 cases were with PHI ≥ 25 (35.9%). Totally, 3680 biopsies (1.1%) of the prostate were performed. As part of the screening, 2870 cases (0.88%) of benign prostatic hyperplasia and prostatic intraepithelial neoplasia were found. Of 742 cases of prostate cancer (0.23%) were revealed. The stages of prostate cancer screening were as follows: stage I in 172 men (23.2%), stage II in 444 men (59.8%), stage III in 98 men (13.2%) and stage IV in 28 (3.8%) men. The indicators of prostate cancer early diagnosis in the I-II stages were bigger in the "screening regions" than in the "traditional diagnostics" regions: RR 1.35 95% CI (1.24 - 1.46), OR 1.84 95% CI (1.58-2.15). Prostate cancer was detected at I-II stages in the "screening" regions only by screening vs traditional diagnostics, with RR 1.64 95% CI (1.56 - 1.73), OR 4.77 95% CI (3.87-5.87). Conclusion: Implementation of screening can improve the diagnosis of prostate cancer in the early stages.